Using Data Analysis Projects to Promote Statistical Thinking in an Introductory Statistics Course: A Basis for Curriculum Materials Development - Rahman, Nik Suryani Nik Abd (EDUCARE, 2014)
ABSTRACT: Statistical thinking has long been a topic of discussion and a generally agreed upon goal for statistics instruction. Statistics involves distinctive and powerful ways of thinking. Statistics is a general intellectual method that applies wherever data, variation, and chance appear. Any introductory course should take as its main goal helping students to learn the basic elements of statistical thinking. Many advanced courses would be improved by a more explicit emphasis on those same basic elements. Those elements were described as: the need for data; the importance of data production; the omnipresence of variability; and the quantification and explanation of variability. The use of data analysis projects provides also students with the opportunity to demonstrate their ability to apply and integrate statistical knowledge and skills in analysing information statistically. This paper will describe the projects and types of statistical analysis that had been selected by 31 counselling students enrolled in an introductory statistics course at the undergraduate level. Content analysis was carried out on their final report of the projects and survey was used to elicit their experiences of working on the projects. These findings will eventually be the basis for the development of curriculum materials to help instructors and their students implement data analysis projects in their respective classrooms.KEY WORDS: Counselling, projects, survey, statistical thinking, statistics, curriculum materials, and undergraduate students.About the Author: Assoc. Prof. Dr. Nik Suryani Nik Abd Rahman is a Senior Lecturer at the Institute of Education IIUM (International Islamic University of Malaysia) in Gombak, Kuala Lumpur, Malaysia. For academic purposes, the author can be contacted via phone: +60192244813 or e-mail: nsuryani@iium.edu.myHow to cite this article? Rahman, Nik Suryani Nik Abd. (2014). âUsing Data Analysis Projects to Promote Statistical Thinking in an Introductory Statistics Course: A Basis for Curriculum Materials Developmentâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.49-56. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 17, 2013); Revised (April 14, 2014); and Published (August 17, 2014).